2016
DOI: 10.1080/10962247.2016.1222317
|View full text |Cite
|
Sign up to set email alerts
|

Source separation of municipal solid waste: The effects of different separation methods and citizens’ inclination—case study of Changsha, China

Abstract: A case study on the source separation of municipal solid waste was performed in Changsha. An effect evaluation method based on accuracy rate and miscellany rate was proposed to study the performance of different separation methods. The site experiment result demonstrates that the two-category (food waste and other waste) method achieves the best effect. The inconsistency between people's inclination and the effect of source separation exists. The proposed method can be expanded to other cities to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 46 publications
(48 reference statements)
3
17
1
Order By: Relevance
“…Inhabitants attitudes and willingness to sort do not have a significant impact on their waste separation behavior. In fact, the results from five articles [18,20,63,67,90] showed that the influence of internal factors such as attitudes, willingness to sort, and environmental knowledge (ability to identify symbols, concepts, and behavior patterns related to environmental protection) together with demographic factors such as income and gender are factors that influence waste separation. These factors appear to be more important than improving the waste management system, e.g., by introducing curbside schemes, different rooms for separation of bulky and electronic waste, or increasing the availability of containers for sorting.…”
Section: Other Non-packaging Factors That Influence Consumer Recyclimentioning
confidence: 99%
See 4 more Smart Citations
“…Inhabitants attitudes and willingness to sort do not have a significant impact on their waste separation behavior. In fact, the results from five articles [18,20,63,67,90] showed that the influence of internal factors such as attitudes, willingness to sort, and environmental knowledge (ability to identify symbols, concepts, and behavior patterns related to environmental protection) together with demographic factors such as income and gender are factors that influence waste separation. These factors appear to be more important than improving the waste management system, e.g., by introducing curbside schemes, different rooms for separation of bulky and electronic waste, or increasing the availability of containers for sorting.…”
Section: Other Non-packaging Factors That Influence Consumer Recyclimentioning
confidence: 99%
“…The review highlights the potential of the visual attributes and the quality of packaging as a communication channel for encouraging consumers to sort the food packaging waste. The efficiency of the waste management system and the quality of recycled products can hence be affected by the proper design of food packaging.Sustainability 2019, 11, 4350 2 of 23 waste management scheme, and in particular in sorting at the source, have been discussed in previous studies [1,6,[16][17][18][19][20][21]. For example, the fractions that are obtained when sorting at the source (e.g., glass, plastic, and paper) have a higher quality compared to fractions obtained when sorting at MRFs, and the source separation process is less expensive [1,3,19].…”
mentioning
confidence: 99%
See 3 more Smart Citations